Fraud Risk Management Approach to Detterence Fraud at Banks in Indonesia - Doni Indrianto; Joseph Antonio Young; Nelson Ng (LAFADZ JAYA Publisher, 2022)
The purpose of this study is to be able to provide information to practitioners to evaluate the understanding and awareness of their bank employees regarding the fraud risk management approach in fraud prevention at banks in Indonesia. This study uses a qualitative descriptive analysis method. This method is used with the aim of describing research results in narrative form. In this study the data used are non-numeric secondary data. Non-numeric secondary data used in the study were found by searching for supporting information for this research from reports, journals, books and websites. The results of this study are that the fraud risk management approach can prevent fraud in the fraud triangle model, as well as detect and respond to fraud that occurs in banks.